Experimental investigation on the strength and stiffness of 3D printed stainless steel S/S-316L parts - Lim, Chee Eng (2019)
The aim of this project is to study the material properties of 3D printed Stainless Steel 316L alloy such as its strength and stiffness to compare with the conventional manufactured Stainless Steel 316L. Material properties are important aspects in engineering which could cause failures. Therefore, it is essential to ensure that safety is not compromised with the benefits of additive manufacturing.